The policy conflict research of interested parties for the efficient management of research equipment: With focus on the government and the scientist - Donghun Yoon (Cogent Business & Management, 2018)
In this paper, the existing research on the policy conflict with regards to the efficient management of research equipment are presented and discussed for the benefit of the interested parties: the government and scientists. The policy improvement and solution plans are then discussed. In the study, a survey was conducted among 30 scientists (10 university scientists, 10 research institute scientists, and 10 enterprise scientists) on the R&D research equipment policy conflict for the policy conflict research of the aforementioned interested parties in relation to the efficient management of research equipment. Based on the survey results, a conflict resolution policy is proposed for the efficient management of research equipment. The results of this research are expected to help resolve the R&D policy conflict and contribute to the management and operation activation of research equipment. Towards these ends, it is hoped that the results of this research will be utilized in laboratories, the basic sciences, and the management and operation activation of research equipment through research result sharing all over the world.
Keywords: 650